Effects of return of endurance training on arterial stiffness and nitric oxide production in elite cyclists - Colin, E.; Tordi, N.; Mourot, L.; Bouhaddi, M.; Regnard, J.; Rouillon, J. D.; Laurant, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Large artery distensibility is physiologically important for circulatory efficiency. It reduces impedance to systolic ejection, cardiac work and slows PWV. Using a non-invasive technique, we have investigated the effect of return of endurance training on the arterial stiffness in 9 elite cyclists. It is well established that arterial stiffness is lower in trained subjects, compared with sedentary. Indeed, exercise training has been reported to produce an improvement in arterial stiffness because of an increase in blood flow in skeletal muscle during repeated bouts of daily exercise. However, the return of training on arterial stiffness in sportsmen is poorly documented, so the purpose of this study was to determine the vascular effects induced by exercise in high trained people. Methods Nine male elite cyclists underwent 2 series of tests. The first series was assessed with the return of the cycling season, and the second was assessed after 16 weeks of endurance training. Two tests were performed at each period: a maximal incremental exercise test with blood samples for determination of plasma nitrate concentration, at rest and during exercise, and a constant exercise test at a workload representing 50 % of the maximal work rate (Wmax) beforehand established, with measure of arterial stiffness using the Pulse Wave Velocity (PWV) between the right common carotid artery and right brachial artery, at rest and during exercise. Results After a program training of 16 weeks, the maximal oxygen consumption (O2max) increased (mean ± SD: from 65.6 ± 5.3 to 70.5 ± 3.4 mL.min-1.kg-1, p < 0.05). Plasma level of nitrate at rest increased after the training program (p < 0.05) (fig. 1). After the training program, PWV was lower at rest (p < 0.05) (fig. 2). During exercise, PWV significantly increased (p < 0.05) in trained subjects, but this increase is less after than before training, without change in blood pressure (fig. 2). Figure 3 shows a significant negative correlation between PWV at rest and O2max (r = - 0.52; p < 0.05). Discussion/Conclusion After training, PWV was lower at rest and during exercise in elite cyclists, suggesting that arterial stiffness was decreased after exercise. In the same way that a training program rapidly increases arterial compliance in untrained subjects, arterial stiffness in trained people could be modified at the return of training. Vascular tone is modulates in part through substances such as NO. Knowing the role of basal release of NO in arterial stiffness, we suggest that the increase of NO production (evaluated by plasma nitrate concentration) contributes to the decrease of PWV at rest in our subjects. The increased of O2max is inversely correlated with a decreased of PWV at rest. This result seem to show that an increase of physical fitness is accompanied with a decrease of arterial stiffness. In conclusion, we suggest that return of chronic endurance training could induce rapidly adaptive changes in vascular function such as endothelium reactivity, with a significant rise of NO production and loss of arterial stiffness.